The promoter of the Arabidopsis nuclear gene COX5b-1, encoding subunit 5b of the mitochondrial cytochrome c oxidase, directs tissue-specific expression by a combination of positive and negative regulatory elements - Welchen, Elina (2004)
In the present work, the promoter of the Arabidopsis thaliana nuclear gene COX5b-1, encoding subunit 5b of the mitochondrial cytochrome c oxidase, has been analysed. For this purpose, plants, stably transformed with different promoter fragments fused to the beta-glucuronidase reporter gene, have been obtained. Histochemical staining indicated that the COX5b-1 promoter directs expression in meristems and in vascular tissues of cotyledons, roots, and hypocotyls, as well as in anthers and pollen and the central leaf vein. Quantitative measurements in extracts prepared from different organs suggested that expression is higher in roots. The analysis of progressive upstream deletions of the promoter suggested the presence of negative regulatory elements, preferentially active in leaves, between nucleotides -609 and -387 from the translation start site. A further deletion down to nucleotide -195 completely abolished expression. The inclusion of sucrose or the cytokinin 6-benzylaminopurine in the culture medium induced COX5b-1 promoter-dependent beta-glucuronidase expression. This induction was observed with all constructs that produced beta-glucuronidase activity. Putative regulatory elements involved in the regulation of other genes were detected in the promoter fragment required for expression. A detailed analysis of these elements will help to elucidate the molecular mechanisms that participate in the expression of this and, possibly, other components of the cytochrome c-dependent respiratory pathway.